Gamifying report text reading: Implementing Wayground to improve vocational students’ comprehension - Shafira, Nasha; Sulistyani, Ummi Nur Laila (Universitas Negeri Semarang, 2025)
This article explores the integration of Wayground, a game-based digital learning platform, as a tool to enhance vocational high school students' comprehension of report texts in English language classrooms. The primary objective of this study is to analyze the pedagogical potential of Wayground in improving students’ reading comprehension, motivation, and active engagement through interactive and student-centered instruction. This research employs a qualitative theoretical approach grounded in literature review, synthesizing findings from recent scholarly sources related to gamification, reading instruction, and the Emancipated Curriculum in Indonesia. Reading report texts presents challenges for vocational students due to their factual, formal, and structured nature, often resulting in disengagement and low comprehension. Wayground offers a practical solution through gamified features—such as instant feedback, time limits, and competitive elements—that stimulate learners’ motivation and cognitive engagement. Furthermore, Wayground facilitates formative assessment and differentiation, supporting individualized learning pathways in line with constructivist principles and curriculum flexibility. The practical implications of this study suggest that integrating Wayground into English reading instruction can revitalize classroom dynamics and improve literacy outcomes in vocational settings. However, considerations such as digital infrastructure and teacher readiness must be addressed to ensure effective implementation. The findings of this study serve as a pedagogical guide for teachers seeking to leverage technology to promote deeper learning and engagement, particularly in reading-intensive lessons.